2012
DOI: 10.1002/app.36278
|View full text |Cite
|
Sign up to set email alerts
|

Role of three different carboxylic monomers in acrylate emulsion copolymerization in the presence of reactive emulsifier

Abstract: In this article, a series of carboxylated acrylate copolymer latices were prepared based on the semicontinuous emulsion polymerization via the pure monomer dropwise manner with three different kinds of carboxylic monomers in presence of reactive emulsifier. The effects of the carboxylic monomers [acrylic acid, methacrylic acid, and monobutyl itaconate (MBI)] on the conversion and the properties of acrylate latices and films have been investigated. The carboxylic groups (ACOOH) distribution of these three kinds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In recent years, the development of soap-free emulsion polymerization [8,9] and reactive surfactants [10][11][12] has promoted the substantial improvement of the resistance to water of the polyacrylate latex films. In order to improve the adhesion properties of polyacrylate emulsions, the tackifying resins especially rosin resin and its derivatives have attracted more and more attentions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of soap-free emulsion polymerization [8,9] and reactive surfactants [10][11][12] has promoted the substantial improvement of the resistance to water of the polyacrylate latex films. In order to improve the adhesion properties of polyacrylate emulsions, the tackifying resins especially rosin resin and its derivatives have attracted more and more attentions.…”
Section: Introductionmentioning
confidence: 99%
“…Significant results obtained by copolymerizing monoitaconates are a possibility of balancing hydrophilic/hydrophobic properties at different pH levels . Lu et al discussed the function of three different carboxylic monomers in acrylate emulsion copolymerization, and found that the latex prepared with MBI has better water resistance than latex with AA. Hence, monoitaconate esters, especially MBI which contains both ester and carboxylic groups, are in high market demand.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few fundamental studies have been carried out concerning the behavior of MBI and β‐CEA in emulsion polymerizations, the distribution of these two new functional monomers between the organic and aqueous phases has not been investigated until now. The partitioning behavior of the carboxylic acids between the organic and aqueous phases depends on many factors such as temperature, pH, composition, type, and concentration of surfactant, etc .…”
Section: Introductionmentioning
confidence: 99%
“…Qu et al 10 reported the synthesis of a series of poly[(n-butyl acrylate)-co-(acrylic acid)] latexes with different particle sizes with changing levels of surfactant at the seed stage. 13,14 They can generally be divided into several categories: unseeded semibatch, 15 monomer-seeded semibatch, 12 and pre-emulsion-seeded semibatch 16 polymerizations. Xu et al 11 discussed the effect of the hard monomer (MMA) content on the adhesive properties of poly(butyl acrylate-co-methyl methacrylate-co-acrylic acid) latexes.…”
Section: Introductionmentioning
confidence: 99%
“…Semibatch polymerizations have always been used in these syntheses of acrylate emulsions. 13,14 They can generally be divided into several categories: unseeded semibatch, 15 monomer-seeded semibatch, 12 and pre-emulsion-seeded semibatch 16 polymerizations. However, no study to date has examined the effect of different semibatch processes on the peel strength of PSAs.…”
Section: Introductionmentioning
confidence: 99%